Biografía : Sauerbruch Hutton (2009)
Breve referencia biográfica sobre los integrantes del estudio.
Keywords: SAUERBRUCH, MATTHÍAS; HUTTON, LOUISA; LUDLOFF, JENS; YOUNG, JUAN LUCAS; KIEL, ANDREW; BARTENSCHLAG, JÜRGEN; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA; BIOGRAFIAS; INGLATERRA; ALEMANIA